Motorola's Droid 2 : the product manager's dilemma - Sawhney, Mohanbir S.; Miniati, John; Kim, Patrick; Goodman, Pallavi ([London] : SAGE, 2016)
After it introduced the extremely successful Droid smartphone into the market in 2009, Motorola quickly moved to develop the next-generation Droid 2 before the next wave of smartphones (including the rumored iPhone 4) flooded the market. The development process was moving smoothly for the company when Verizon, its biggest partner, dropped a bombshell: It wasn't happy with the mechanical camera button on the Droid 2 and wanted it to be changed to a software button like the iPhone's. This case explains how Motorola dealt with this awkward dilemma.
Originally Published in: Sawhney, M., Miniati, J., Kim, P., & Goodman, P. (2014). Motorola's Droid 2: The Product Manager's Dilemma. 5-313-510. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Motorola, Inc; Product design -- Case studies; Communication in organizations -- Case studies; Negotiation in business -- Case studies